THE SYSTEM OF CLUSTER ANALYSIS OF RESULTS OF NON-DESTRUCTIVE CONTROL OF WARES IS FROM COMPOSITION MATERIALS ON BASIS OF NEURON NETWORK OF KOKHONENA - Єременко, В. С.; Переїденко, А. В.; Роганьков, В. О. (Science-based technologies, 2009)
This article is devoted to realization system of the cluster analysis without etalon samples. Main different vectorspace metrics аre analyzed using the special control system. System was created with NI LabVIEW 8.5.